Changes of mind an essay on rational belief revision - Tennant, Neil, 1950- (Oxford : Oxford University Press, 2012)
An account of how a rational agent should revise beliefs in the light of new evidence. Computationally implementable, it provides rigorous mathematical theory of dependency networks and investigates the complexity of algorithms for rational agents revising beliefs.
Description based on online resource; title from PDF title page (viewed on July 16, 2012).
Includes bibliographical references and index.
Keywords: Belief and doubt; Rationalism